Factors Promoting Community Strengthening: A Case Study of Dusong Yo Sub-District, Chanae District, Narathiwat Province - ยูนุ , นูรมีมี; สาเม๊าะ, ไลลา; ดาโอ๊ะ, มูฮำหมัดคาน ดาโอ๊ะ; สุขเสนีย์, คมวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aims to 1) study the factors that promote community strengthening in Dusongnyo Subdistrict, Chanae District, Narathiwat Province, and 2) study the guidelines for promoting community strengthening in Dusongnyo Subdistrict, Chanae District, Narathiwat Province. The research employed a qualitative research method with key informants including one Dusongnyo Subdistrict Administrative Organization Chairman, one Dusongnyo Subdistrict Headman, one Provincial Administrative Organization Council member, one Dusongnyo Subdistrict Village Headman, one government official, one Dusongnyo Subdistrict policy analyst, and six citizens, totaling 12 individuals. Data was collected using purposive sampling and in-depth interviews. Data was analyzed using content analysis, categorizing and systematizing the information, then interpreting and drawing inductive conclusions. The data was then presented as descriptive statements.            The research results found that 1) the factors that promote community strength are 5 aspects: (1) individual or human capital, (2) quantity and quality of activities, (3) materials or environment, (4) peer capital or network, and (5) status of community organizations, with local, local and religious leaders working together, and people participating in various activities. 2) the approaches to promoting community strength are 5 aspects: (1) educational approach, (2) quality of activities approach, (3) quality and environment approach, (4) religious activities approach, and (5) systematic work approach.